THE INFLUENCE OF STAKEHOLDER ENGAGEMENT AND TRANSFORMATIONAL LEADERSHIP ON BUSINESS SUSTAINABILITY - Susanti Kurniawati; Ardika Sulaeman (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2022)
This research is motivated by the low sustainability of soybean-based MSMEs (Micro Small Medium Enterprises) in West Java. This is due to the low long-term value given to stakeholders in the economic, social and environmental dimensions and the less-than-optimal role of leaders in realizing business sustainability. The purpose of this study is describing the business sustainability, stakeholder engagement, transformational leadership and analyzing the effect of transformational leadership and stakeholder engagement on business sustainability. This research was conducted using a survey method on 254 soybean-based SMEs consisting of tempe, tofu and soy sauce craftsmen in West Java. Data was collected by distributing a questionnaire, interviewing and observations of the unit of analysis. The data that has been collected was analyzed using structural equation modeling (SEM) analysis techniques. The results of this study stated that the business sustainability of soybean-based MSMEs was actually better in the social dimension and relatively less in the environmental dimension. The ability of transformational leaders to influence their employees to achieve goals is the highest ability, while the ability of forward-looking is the lowest than other dimensions. In building stakeholder engagement, the leader's ability to build trust is the highest, while business openness is the lowest compared to other capabilities. In this study, transformational leadership and stakeholder engagement affect business sustainability partially and simultaneously.